THE CHARACTER THUY KIEU IN THE TALE OF KIEU FROM THE PERSPECTIVE OF CONFUCIAN CULTURE - Phạm Văn Hóa (Tạp chí Khoa học Đại học Đà Lạt)
Ethical Confucianism in general imparts into Vietnamese cultural life not only moral standards, the embodiment of Confucian morality, but also the embodiment of the people’s morality to dream as it exists in reality and is protected by the Vietnamese people. This article analyzes the following aspects of Thuy Kieu's character: loyalty, honor, chastity, and gratitude from the perspective of interdisciplinary literature and culture, particularly Confucian culture. Nguyen Du's loyalty, honor, chastity, and gratitude in Thuy Kieu, of course, partly comes from the Confucianism tradition, but most importantly, from rich love and humanity; it is what Vietnamese people live for. This article affirms that loyalty, honor, chastity, and gratitude in Thuy Kieu, although called Confucianism, are in fact the qualities of the Vietnamese people. Thuy Kieu's personality shows that Confucian morality has been re-conceptualized by the nation's traditions, by the reality of contemporary society, and also by the living environment of Nguyen Du, himself. And more importantly, that "morality" is inspired again, imbued with a loving soul, a great personality, and a noble philanthropic spirit. This article shows that “The Tale of Kieu” is not simply a copy of an earlier work.